Chinese students' pronunciation errors in Arabic speaking skills - Ali, Asem Shehadeh Saleh; Wei, Jing (IIUM Press, 2025)
This study investigates pronunciation errors in Arabic among Chinese students at the International Islamic University Malaysia (IIUM). Pronunciation is crucial for mastering a language, as it serves as a fundamental skill for effective communication. Research indicates that a person's first language significantly influences their pronunciation of a second language, often leading to difficulties and errors. The distinct differences between Chinese and Arabic pronunciation pose considerable challenges for Chinese native speakers learning Arabic as a second language. Given that pronunciation is a key component of language acquisition, it is essential to conduct a thorough examination of these issues to understand students' pronunciation challenges and their underlying causes. This understanding can aid both teachers and students in developing effective pedagogical strategies and solutions. To accomplish the objectives of this study, one researcher conducted in-depth interviews with Chinese students from various Kulliyyahs at IIUM and recorded their pronunciation for comparative analysis. The results reveal that the most challenging sounds for Chinese students are those that do not exist in Mandarin, such as (أ، ه، ح، خ، ع، غ، ص، ط، ظ، ض), among others. These findings highlight the need for targeted instructional approaches that address specific phonetic difficulties. In conclusion, the researcher proposes solutions based on the identified challenges and their root causes, which could significantly enhance the Arabic learning experience for Chinese students